Sustainable human development; issues and challenges - Taori, Kamal (Delhi, 2000)
This book is an attempt to codify various experiences which can help and facilitate acceleration of smooth change. There are no permanent solutions because there can never be, but, some direction is proposed in this regard. While part one tackles various marketing issues, part two looks at the training attitude and part three examines some policy issues.
Keywords: Sustainable dcevelopment